Physical Activity, Body Composition, Physical Fitness, and Body Dissatisfaction in Physical Education of Extremadura Adolescents: An Exploratory Study - María Isabel Moreno-Díaz; Miguel Vaquero-Solís; Miguel Ángel Tapia-Serrano; Pedro Antonio Sánchez-Miguel (MDPI AG, 2024)
In recent years, physical activity levels among youths have declined significantly. This has led to a decline in adherence to physical activity recommendations. In this sense, physical education offers an ideal environment that contributes positively to improving adherence to physical activity recommendations, as it teaches students movement-related skills and knowledge. The objective of the present research was to investigate the relationship between physical activity levels, body composition, fitness in Physical Education, and body dissatisfaction levels, and to analyse sex differences in relation to the study variables. The sample was formed of 1166 participants from the 1st and 2nd secondary compulsory education, of which 642 were boys (age 13.16 ± 0.91), and 524 girls (age 13.08 ± 0.85). The measure of physical activity was the Physical Activity Questionnaire for Adolescents (PAQ-A). Body composition was assessed using weight and height to calculate their body mass index. Cardiorespiratory capacity was assessed using the Course-Navette test in Physical Education lessons. The results showed the relationship between physical activity and body mass index, cardiorespiratory capacity, and body satisfaction. It was also confirmed that higher levels of physical activity were associated with a lower body mass index, improvements in cardiorespiratory fitness, and lower levels of body dissatisfaction to a greater extent in boys than in girls. The study concludes that improvements in the study variables were associated with increased physical activity. In addition, it seems necessary to promote healthy lifestyles in physical education lessons, especially during adolescence, as they could serve as a gateway for the improvement of health-related fitness in future generations. Increasing the amount of physical activity among young people is vital. Therefore, it would be essential to develop intervention programs in physical education classes, especially during adolescence, aimed at promoting and increasing physical activity and its benefits.